Elevated Troponin I and Low Serum Magnesium Levels are Suggestive of Greater Cardiac Damage in Acute Myocardial Infarction (Mediscope, 2025)
Background: Myocardial infarction (MI) is a common and widespread disease in the present world. Magnesium has been considered an important factor in the pathogenesis of acute myocardial infarction and its complications. Also, in response to myocardial injury cardiac Troponin I (cTnI) is released into the blood. This biomarker is widely used for determining myocardial infarction since its serum value is frankly proportional to the area of infarction. The association between serum magnesium levels and Troponin I denotes a negative correlation suggesting major adverse outcomes in patients of Acute Myocardial Infarction.Objective: This study aimed to illuminate the association between magnesium levels and area of infarction. Thus, we compared serum levels of magnesium and Troponin I in Acute Myocardial Infarction patients.Methods: This cross-sectional descriptive study was conducted in the Department of Pharmacology & Therapeutics, Rajshahi Medical College (RMC), Rajshahi, in collaboration with the Cardiology Department of RMC between July 2019 to June 2020. Assessment and comparison of Troponin I and serum magnesium levels in 50 patients of acute MI was done in this study.Results: The mean Troponin I level of respondents with complications was 7.44±6.92 and in patients without complications it was 2.17±2.09. Troponin I level was higher in patients with complications than those who had no complications. On comparison which was statistically significant. (p-value